2006
DOI: 10.1007/s10067-006-0325-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of early and refractory dermatomyositis with infliximab: a report of two cases

Abstract: The idiopathic inflammatory myopathies embody the largest group of acquired and potentially treatable causes of skeletal muscle weakness. The three major groups of this disorder are polymyositis (PM), dermatomyositis (DM), and inclusion body myositis. Corticosteroids continue to be the mainstay of initial treatment in the majority of cases of PM/DM. The treatment of refractory disease can be challenging despite the utilization of the medications currently available. We report two patients with refractory DM wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 17 publications
0
25
0
4
Order By: Relevance
“…: infliximab, etanercept, adalimumab) may be helpful in the therapy of patients with active refractory PM/DM. In our literature review, we have, in fact, found 18 case reports of patients with resistant myositis (ten DM, eight PM) who successfully took infliximab at a dose of 3-10 mg/kg/day; improvement of muscle strength was observed in 94.1% of patients [131][132][133][134][135][136][137][138][139][140]. Twenty-eight additional patients (12 DM, 16 PM) were given etanercept (25 mg twice weekly subcutaneously); muscle strength improved in only 39.3% of patients [133,[138][139][140][141].…”
Section: Tnf-a Antagonistsmentioning
confidence: 93%
“…: infliximab, etanercept, adalimumab) may be helpful in the therapy of patients with active refractory PM/DM. In our literature review, we have, in fact, found 18 case reports of patients with resistant myositis (ten DM, eight PM) who successfully took infliximab at a dose of 3-10 mg/kg/day; improvement of muscle strength was observed in 94.1% of patients [131][132][133][134][135][136][137][138][139][140]. Twenty-eight additional patients (12 DM, 16 PM) were given etanercept (25 mg twice weekly subcutaneously); muscle strength improved in only 39.3% of patients [133,[138][139][140][141].…”
Section: Tnf-a Antagonistsmentioning
confidence: 93%
“…Infliximab showed benefit in patients with refractory DM complicated by bulbar weakness and ventilatory failure [67] or pneumatosis cystoides intestinales [68]. Patient deaths resulted from a presumed opportunistic lung infection with Mycobacterium peregrinum [69], or from aspiration pneumonia complicated by multi-organism bacteremia soon after the first infusion of a second course of infliximab [71]. Possible complications partly ascribed to anti-TNFa therapy were methicillinresistant Staphylococcus aureus pneumonia and diffuse, large B cell non-Hodgkin's lymphoma [63], and necrotizing fasciitis due to oxacillin-resistant S. aureus [73]; however, any cause-effect relationship was confounded by the recognized association between DM and malignancy [74], and by the fact that patients had also been exposed to combination immunosuppressive therapy.…”
Section: Case Reportsmentioning
confidence: 97%
“…While early case series reported positive effects [80][81][82][83][84][85][86], there has been increasing concern over these drugs due to some recent reports of disease flares or the initiation of myositis with TNF-α therapies [87][88][89][90]. An open-label study looking at the efficacy of infliximab combined with methotrexate was terminated owing to a low inclusion rate and a high dropout rate due to disease progression or side effects [91].…”
Section: Cytokine-based Therapiesmentioning
confidence: 99%